DOI: 10.21007/etd.cghs.2016.0405
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Zoonotic Potential of a Novel Bovine Influenza Virus

Abstract: for your guidance as I pursued my doctoral degree. I sincerely appreciate the time which you invested in my education and the opportunity to learn from scientists whom I regard with so much respect. Last, I thank my mentor Dr. Richard Webby for the opportunity to work in your lab and for your mentorship. I learned not only how to think scientifically but how to act as a leader. I have no doubt that the lessons learned in my doctoral education will benefit me for the rest of my career.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 107 publications
0
12
0
Order By: Relevance
“…Serologic assays in two independent studies showed that IDV could potentially infect humans, although seropositivity rates in the studies differed. One of the studies reported 91% seropositivity among 35 persons working with cattle (White et al, 2016), and the other reported only 1% seropositivity among 741 persons with suspected high exposure to IDV (Eckard, 2016). Nevertheless, epidemiologic, serologic, and pathologic studies have suggested cattle are the primary natural reservoir for IDV (Collin et al, 2015; Ducatez et al, 2015; Ferguson et al, 2015; Ferguson et al, 2016; Hause et al, 2014; Jiang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Serologic assays in two independent studies showed that IDV could potentially infect humans, although seropositivity rates in the studies differed. One of the studies reported 91% seropositivity among 35 persons working with cattle (White et al, 2016), and the other reported only 1% seropositivity among 741 persons with suspected high exposure to IDV (Eckard, 2016). Nevertheless, epidemiologic, serologic, and pathologic studies have suggested cattle are the primary natural reservoir for IDV (Collin et al, 2015; Ducatez et al, 2015; Ferguson et al, 2015; Ferguson et al, 2016; Hause et al, 2014; Jiang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of animals susceptible to IDV, including sheep, goats [ 6 ], ferrets [ 3 ], and guinea pigs [ 7 ]. Importantly, serological studies have shown that a low percentage of human sera have detectable titers of specific antibodies against the influenza D viruses [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Serological studies show the presence of IDV in beef cattle at least since 2004 (5). Bovine species are the main reservoir for IDV.…”
Section: Introductionmentioning
confidence: 99%
“…ICV infection is characterized by mild clinical respiratory illness with a low frequency of infection, commonly in young and elderly individuals (24). IDV can infect ferrets, but has not transmitted from human to humans to date (4,5). ICV has a global distribution in children (25), and is reported in pigs (26), dogs (27), and camels (28).…”
Section: Introductionmentioning
confidence: 99%